2011
DOI: 10.18632/oncotarget.255
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 in sarcomas: friend or foe?

Abstract: Sarcomas represent a heterogeneous group of tumors with a complex and difficult reproducible classification. Their pathogenesis is poorly understood and there are few effective treatment options for advanced disease. Caveolin-1 is a multifunctional scaffolding protein with multiple binding partners that regulates multiple cancer-associated processes including cellular transformation, tumor growth, cell death and survival, multidrug resistance, angiogenesis, cell migration and metastasis. However, ambiguous rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…95 By analogy, even the role of Cav-1 in cancer appears to be ambiguous, because Cav-1 may behave as either a tumor suppressor or oncopromoter depending on the type of tumor. [96][97][98][99][100][101] Our data argue for an important role of Cavin-1 as essential partner of Cav-1 in RMS progression, as we clearly observed that loss of either Cavin-1 or Cav-1 was sufficient to impair cell proliferation, migration and anchorage-independent cell growth, a characteristic predictive of cell transformation in vitro and in vivo. Consistent with this, we also found that an incremental expression of Cavin-1 in RD cells, as causally obtained upon Cav-1 overexpression, led to a very aggressive cell behavior, which was characterized by a remarkable anchorage-independent cell growth.…”
Section: Discussionsupporting
confidence: 58%
“…95 By analogy, even the role of Cav-1 in cancer appears to be ambiguous, because Cav-1 may behave as either a tumor suppressor or oncopromoter depending on the type of tumor. [96][97][98][99][100][101] Our data argue for an important role of Cavin-1 as essential partner of Cav-1 in RMS progression, as we clearly observed that loss of either Cavin-1 or Cav-1 was sufficient to impair cell proliferation, migration and anchorage-independent cell growth, a characteristic predictive of cell transformation in vitro and in vivo. Consistent with this, we also found that an incremental expression of Cavin-1 in RD cells, as causally obtained upon Cav-1 overexpression, led to a very aggressive cell behavior, which was characterized by a remarkable anchorage-independent cell growth.…”
Section: Discussionsupporting
confidence: 58%
“…Llombart-Bosch et al observed an expression of CAV1, which is also a direct target of the EWSR1-FLI1, in 96 % of 385 ES samples [43]. However, the expression of CAV1 has been reported in several other sarcomas, including osteosarcomas and rhabdomyosarcomas [44]. Therefore, these markers might be sensitive for ES, but in view of the lack of specificity, their diagnostic use remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoreactivity of CAV1 in lung carcinoma is histotype-dependent and CAV1 expression is negative in 85% of lung carcinomas [7]. The majority of primary osteosarcoma and alveolar rhabdomyosarcoma tumors showed significantly lower levels of CAV1 than normal tissues, suggesting its role as a tumour suppressor [8]. In addition, CAV1 expression is associated with better overall survival for osteosarcoma patients [8].…”
Section: Introductionmentioning
confidence: 99%